Contribute of crude glycerin to increase the efficiency of anaerobic digestion process of dairy cattle manure - Simm, Silvana; Amorim Orrico, Ana Carolina; Previdelli Orrico Junior, Marco Antonio; Sunada, Natalia da Silva; Schwingel, Alice Watte [UNESP]; Teixeira Lopes, Walter Renato; Whittinghill, Karla Lima; Vargas, Fernando Miranda de; Silva de Mendonca Costa, Monica Sarolli (Wiley-Blackwell, 2018)
The objective of this study was to determine the optimal inclusion doses of crude glycerin in anaerobic co-digestion with dairy cattle manure processed at 10, 17, and 24 days of retention in order to maximize reductions in solid and fibrous constituents and increase the productions of biogas and methane. Semi-continuous digesters were fed with daily loads of substrates containing doses of 0, 5 and 10% (based on total solids, TS) of crude glycerin and dairy cattle manure. The highest specific productions of biogas and methane with the 10-day HRT were also achieved in substrates with 0% glycerin, reaching values of 0.91 and 1.27 L/g of TS and solids (VS) added, respectively. In substrates retained for 17 and 24 days the values were maximal with addition of glycerin doses between 2.7 and 3.6% resulting in yields of 1.72 and 2.42 L of biogas per gram of TS added and 2.37 and 3.31 L of biogas per gram of VS added, respectively. For methane production, the optimal inclusion doses of crude glycerin with HRTs of 10, 17, and 24 days were 0.0, 3.7, and 3.3%, generating 0.70, 1.43, and 1.86 L of methane per gram of VS added. The inclusion of crude glycerin in co-digestion with dairy cattle manure is not recommended for digesters operated with retention time of 10 days. However, when substrates remain for 17 or 24 days this inclusion promotes reductions of solids constituents while maximizing the specific productions of biogas and methane. (c) 2017 American Institute of Chemical Engineers Environ Prog, 37: 1305-1311, 2018
Keywords: biogas; glycerol; methane; hydraulic retention time